ALUMNI PERCEPTION OF THE ROLE OF ENGLISH LEARNING IN PREPARING FOR A CAREER IN THE PROPERTY SECTOR - Bedah, Bedah; Fitriani, Dini; Kheryadi, Kheryadi (Universitas Tanjungpura, 2026)
This study explores the perceptions of vocational High School alumni regarding the role of English learning in preparing students for careers in the property sector, particularly construction and real estate development. Using a qualitative approach, the study involved seven alumni from the building Engineering major who are currently working in the property industry. Data were collected through in-depth interviews and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that English plays a significant role in enhancing graduates career readiness. Speaking, writing, and vocabulary skills are identified as the most essential competencies in the workplace. English proficiency supports alumni in communicating with clients, understanding technical documents, and improving professional performance. However, English instruction in vocational school still predominantly emphasizes General English, which dose not adequately address industry needs. Therefore, the study highlights the importance of implementing English for Specific Purpose (ESP) by integrating technical vocabulary, project-based communication, and industry-relevant negotiation simulation to better align education with workplace demands.